An Analytical study of al-maqamah al-mushajariyah in al-Ilory’s maqamat. المقامة المشجرية في مقامات الإلوري:دراسة تحليلية (2014)
This research deals with a new topic which had not been favorably studied before, and by the time several studies were being written about Arabs Maqamats like those of al-Hamadhani's Maqamah, al-Hariri's Maqamah and etc. On this, Nigeria maqamats are still in need of study being a virgin work in Nigerian literary output. Therefore, this work is aiming to study the literary and critical study of Maqamah al-Mushajariyyah in Al-IIory’s Maqamah of Sheikh Muhammad –l- Awwal Abdul Salam known as Sahibul-Qur’an. Before delving in to the main topic, this research would firstly focuses on the meaning of Maqamah and its significances, likewise it would discuss briefly about the historical background of Sahibul-Qur’an.